Insight into the hydrogen migration processes involved in the formation of metal-borane complexes: Importance of the third arm of the scorpionate ligand - Tsoureas, Nikolaos; Hamilton, Alex; Haddow, Mairi F.; Harvey, Jeremy N.; Orpen, A Guy; Owen, Gareth R. (Organometallics, 2013)
The reactions of [Ir(κ3N,N,H-Tai)(COD)] and [Ir(κ3N,N,H-PhBai)(COD)] (where Tai = HB(azaindolyl)3 and PhBai = Ph(H)B(azaindolyl) 2) with carbon monoxide result in the formation of Z-type iridium-borane complexes supported by 7-azaindole units. Analysis of the reaction mixtures involving the former complex revealed the formation of a single species in solution, [Ir(η1-C8H 13){κ3N,N,B-B(azaindolyl)3}(CO) 2], as confirmed by NMR spectroscopy. In the case of the PhBai complex, a mixture of species was observed. A postulated mechanism for the formation of the new complexes has been provided, supported by computational studies. Computational studies have also focused on the reaction step involving the migration of hydrogen from boron (in the borohydride group) to the iridium center. These investigations have demonstrated a small energy barrier for the hydrogen migration step (ΔG298 = 10.3 kcal mol-1). Additionally, deuterium labeling of the borohydride units in Tai and PhBai confirmed the final position of the former borohydride hydrogen atom in the resulting complexes. The importance of the "third azaindolyl" unit within these transformations and the difference in reactivity between the two ligands are discussed. The selective coordination properties of this family of metallaboratrane complexes have also been investigated and are discussed herein. © 2013 American Chemical Society.